Transversality conditions for the existence of solutions of first-order discontinuous functional differential equations - Pouso, Rodrigo López; Albés, Ignacio Márquez; Rodríguez-López, Jorge (Topological Methods in Nonlinear Analysis, 2021)
We are concerned with the existence of extremal solutions to a large class of first-order functional differential problems under weak regularity assumptions. Our technique involves multivalued analysis and the method of lower and upper solutions in order to obtain a new existence result to a scalar Cauchy problem. As a consequence of this result and a monotone iterative method for discontinuous operators, we derive our main existence result which is illustrated by several examples concerning well-known models: a generalized logistic equation or second-order problems in the presence of dry friction.